Pengetahuan dan Persepsi Keluarga Penderita Penyakit Ginjal Tahap Akhir (PGTA) terhadap Transplantasi Ginjal di RS Hasan Sadikin Bandung - Syakira, Rizqa Adinda; Mariani, Helni; Andhika, Rizky (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. Kidney transplantation is the best kidney replacement therapy for End Stage Renal Disease (ESRD) patients. The gap between the number of donors and recipients remains a problem contributing to the low rate of kidney transplantation in Indonesia. The families of ESRD patients are the most recommended donor candidates. Knowledge and perception have a crucial role in the decision to donate organs, making it important to know the knowledge and perception of ESRD patients’ families towards kidney transplantation. This study aimed to describe the knowledge and perception of families of ESRD patients undergoing dialysis at Dr. Hasan Sadikin General Hospital Bandung. Methods. A descriptive quantitative study with a cross-sectional approach was conducted on the families of patients in the Dialysis Unit of Dr. Hasan Sadikin General Hospital, Bandung, aged ≥26 years, selected through consecutive sampling. Respondents were chosen if they had a blood relationship or emotional connection with patients undergoing hemodialysis or Continuous Ambulatory Peritoneal Dialysis (CAPD). Data collection was carried out from December 2023 to February 2024 using a validated questionnaire. The questionnaire items were developed based on several research studies on similar topics. Knowledge levels were measured through three variables: concepts, selection, and factual events. Meanwhile, the perception aspect assessed prosocial personality, post-transplant risk, and confidence in the procedure. Descriptive data analysis was performed using SPSS version 25. Results. A total of 107 respondents met the inclusion criteria, with the majority aged 26–35 years (34.6%) and predominantly female (69.2%). The majority of respondents were characterized by good knowledge (53.3%) and positive perceptions (65.4%). Within the knowledge domain, the highest proportion of correct responses was observed for items related to donor requirements (98.1%), whereas the lowest was noted for items addressing the conceptual understanding of kidney transplantation procedures (25.2%). In terms of perception, the most favorable responses were associated with the concept of severance of family ties, while the most negative responses were linked to concerns regarding the risks of post-transplant complications. Conclusions. Most respondents have a good level of knowledge and positive perceptions towards kidney transplantation. The greatest fear among respondents was related to the transplant procedure and the risks of post-transplant complications. This study highlights the need for educational interventions to improve the knowledge and perceptions of ESRD patients’ families concerning aspects of kidney transplantation that remain insufficiently understood.